SURVEY OF INPATIENT SATISFACTION AT VIET TIEP FRIENDSHIP HOSPITAL, AN DONG BRANCH 2, 2025 (Vietnam Journal of Community Medicine, 2026)
Problem Statement: In hospital quality management, patient satisfaction is a crucial output indicator reflecting the competence and quality of healthcare services. In accordance with Decision No. 56/QD-BYT dated January 8, 2024, of the Ministry of Health, which guides the measurement of satisfaction with public healthcare services for the period 2024–2030, healthcare facilities need to periodically evaluate and improve the quality of their services. Based on this practical requirement, this study was conducted to describe the satisfaction of inpatients at Viet Tiep Friendship Hospital, An Dong Branch 2, as a basis for proposing solutions to improve service quality.Objective: This study describes residents' satisfaction at the Vietnam-Czech Friendship Hospital, An Dong branch, Hai Phong city, in 2025.Research method: A cross-sectional descriptive study was conducted through a survey of 230 inpatients at Viet Tiep Friendship Hospital, An Dong Branch 2, from July 2025 to September 2025. The study used Google Sheets for data entry and processing, then transferred the data to Stata 17 for statistical analysis.Results: The study showed that the satisfaction scores of the research subjects regarding the quality of medical examination and treatment services across five aspects were as follows: satisfaction score regarding accessibility was 4.8/5 points; satisfaction score regarding transparency of information and examination and treatment procedures was 4.78/5 points; satisfaction score regarding facilities and equipment serving patients was 4.76/5 points; satisfaction score regarding the attitude and professional competence of medical staff was 4.81/5 points; and satisfaction score regarding the results of service delivery was 4.79/5 points.Conclusion: The average satisfaction score of inpatients at Viet Tiep Friendship Hospital, An Dong Branch 2, is 4.78 ± 0.41 (very satisfied). The rate of patients who will definitely return and refer others is 96.5%.
Keywords: Inpatient patient satisfaction, Viet Tiep Friendship Hospital, Hai Phong City